2021
DOI: 10.1055/s-0040-1722744
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Hernias: An Epidemiological Profile and Surgical Experience from a Rural Medical College in Central India

Abstract: Background Abdominal wall hernia is a common surgical entity worldwide with groin hernias having the most common presentation among them. They are a cause of morbidity and mortality if not addressed in time. A variety of surgical methods are available for the repair of hernias. The tension-free repair using synthetic mesh has the least recurrence and is the most accepted. Aim To describe the surgical burden and clinical profile of abdominal wall hernias as well as experiences in their management in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
9
1
Order By: Relevance
“…Preferred approach in a patient with symptomatic hernia, BMI > 40 kg/m 2 In an algorithm that was published in 2020, the recommendation suggested if there is an abdominal or an incisional hernia, for symptomatic cases and all defect sizes, a hernia repair should be followed by bariatric surgery. If the hernia is < 4 cm (W1) and asymptomatic, then concomitant bariatric surgery should be done with hernia repair.…”
Section: Adhesions Occur In Ipom With a Coated Meshmentioning
confidence: 99%
See 2 more Smart Citations
“…Preferred approach in a patient with symptomatic hernia, BMI > 40 kg/m 2 In an algorithm that was published in 2020, the recommendation suggested if there is an abdominal or an incisional hernia, for symptomatic cases and all defect sizes, a hernia repair should be followed by bariatric surgery. If the hernia is < 4 cm (W1) and asymptomatic, then concomitant bariatric surgery should be done with hernia repair.…”
Section: Adhesions Occur In Ipom With a Coated Meshmentioning
confidence: 99%
“…The prevalence of abdominal wall hernias is 1.7% for all ages and 4% for those over 45 years, making them a relatively common condition. Worldwide, an estimated 20 million patients with hernias are treated each year [2]. A ventral (abdominal wall) hernia is surgically repaired.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the vast majority of the umbilical hernia defects that can be seen in infancy, will self-obliterate by the 5th year of age in more than three quarters of the patients [16]. With respect to those hernias arising during adult life, any factor which can increase the intra-abdominal pressure (obesity, ascites, chronic cough, pregnancy, chronic straining due to constipation) or weaken the strength of the anterior abdominal wall (connective tissue diseases, smoking, auto-immune disorders), could be implicated in their pathogenesis [17].…”
Section: Types Of Ventral Herniasmentioning
confidence: 99%
“…[1][2][3] Patients who have cirrhosis, obesity or multiparous women are the groups most likely to experience PUH. [1][2][3][4] The most popular approach over the past century for the resolution of PUH has been herniorrhaphy with simple suture or Mayo's repair (vest over pants). 5 However, numerous retrospective studies have shown that these procedures have an abnormally high recurrence (10-30%).…”
Section: Introductionmentioning
confidence: 99%